Rancang Bangun Sistem Pemesanan Obat Di Apotek Diva Berbasis Website (Studi Kasus : Apotek Diva) - Indah Mardianti Tanjung; Irene Mareta Widya Ningtyas; Sherlinda Irdianov; Farizi Ilham (CV. Multi Kreasi Media, 2025)
Existing studies have demonstrated that digital pharmacy platforms significantly enhance transaction speed and streamline inventory management processes (Julita et al., 2025). However, Apotek Diva continues to experience operational challenges due to the absence of an online ordering system and suboptimal public dissemination of its pharmaceutical services. This study employs the Waterfall methodology to design and implement a web-based drug inventory system, building upon its proven effectiveness in managing transactions and sales reporting as evidenced in Apotek Riski Sehat Jakarta's implementation (Nilawati et al., 2022). Data collection incorporated participatory observation techniques and in-depth interviews conducted at Apotek Diva. The developed system features comprehensive drug cataloging, online ordering capabilities, multiple delivery options, and administrative data management tools. Utilizing PHP and MySQL with UML modeling support - an approach that yielded significant efficiency improvements in data and transaction handling at Apotek Mitra Sehat (Rahmadani, Harris & Hendri, 2023) - the implemented solution has successfully enhanced customer ordering convenience while optimizing Apotek Diva's operational efficiency.